Jacques Lacan : a feminist introduction - Grosz, Elizabeth (London ; New York : Routledge, 1990)
"Grosz gives a critical overview of Lacan's work from a feminist perspective. Discussing previous attempts to give a feminist reading of his work, she argues for women's autonomy based on an indifference to the Lacanian phallus." http://catdir.loc.gov/catdir/enhancements/fy0648/89011005-d.html
1. Psychoanalysis and scandal -- 2. The ego and the imaginary -- 3. Sexuality and the symbolic order -- 4. Language and the unconscious -- 5. Sexual relations -- 6. Lacan and feminism.
Includes bibliographical references (pages 206-213) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Lacan, Jacques, -- 1901-1981.; Lacan, Jacques, -- 1901-1981; Freud, Sigmund, -- 1856-1939; Lacan, Jacques, -- 1901-1981.; Lacan, Jacques; Lacan, Jacques, -- 1901-1981; Lacan, Jacques, -- 1901-1981 -- Criticism and interpretation; Psychoanalysis and feminism; Psychoanalysis; Psychoanalytic Theory; Women -- psychology; Psychoanalysis; Psychanalyse et féminisme.; Psychanalyse; psychoanalysis; PSYCHOLOGY -- Movements -- Psychoanalysis; Psicoanálisis y feminismo; Psychoanalysis and feminism; Psychoanalyse; Feminisme; Sexo e sexualidade (sociologia); Mulher e feminismo; Psicanalise; Feminist criticism; Psychoanalysis and feminism; Psychoanalysis -- Lacan, Jacques, 1901-1981; Electronic books; Biographies